The correlations among English language exposure, learning motivation, and reading comprehension achievement of high school students in Palembang - Galiansa Galiansa; Bambang A Loeneto; Mgrt. Dinar Sitinjak (English Review: Journal of English Education, 2020)
Language exposure and learning motivation are two of the most essential aspects in learning any language. In English language acquisition, the development of these two components facilitates the development of other language skills, such as reading comprehension. In turn, reading comprehension is one of the significant indicators of fluency in second or foreign language acquisition. If a correlation can be determined between either language exposure or learning motivation and the development of reading comprehension, educators and specialists can focus their efforts on increasing these predictor variables in curriculum development to further reading comprehension and, ultimately, fluency. This study focused on the reading comprehension of senior high school students in Palembang, Indonesia and sought to find out whether or not there was any significant correlation between students’ English language exposure and reading comprehension, students’ learning motivation and reading comprehension, and among the predictor variables (English language exposure, learning motivation) and the criterion variable (reading comprehension). The samples of this study were 210 eleventh graders in SMA Unggulan, a high-performing senior high school in Palembang. The data were analyzed by using correlational and regression analyses. The findings showed significant positive correlations among English language exposure, learning motivation, and reading comprehension. The contribution of English language exposure to reading comprehension was 41.8%, while the contribution of learning motivation to reading comprehension was 51.7%. Moreover, the contribution of predictor variables to the criterion variable was 58.9%.